2010
DOI: 10.1128/jb.01324-09
|View full text |Cite
|
Sign up to set email alerts
|

A DNA-Binding Peroxiredoxin of Coxiella burnetii Is Involved in Countering Oxidative Stress during Exponential-Phase Growth

Abstract: Coxiella burnetii is a Gram-negative, obligate intracellular bacterial pathogen that resides within the harsh, acidic confines of a lysosome-like compartment of the host cell that is termed a parasitophorous vacuole. In this study, we characterized a thiol-specific peroxidase of C. burnetii that belongs to the atypical 2-cysteine subfamily of peroxiredoxins, commonly referred to as bacterioferritin comigratory proteins (BCPs). Coxiella BCP was initially identified as a potential DNA-binding protein by two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Anti-rLimB and anti-rCom1 polyclonal antibodies were generated in female New Zealand white rabbits, as described previously (Parrow et al, 2009), using 100 mg purified rLimB or rCom1 (Hicks et al, 2010) for both primary and booster injections. Rabbit anti-MBP polyclonal antibodies were purchased (NEB) and used as a negative control for the LimB fusion protein partner.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-rLimB and anti-rCom1 polyclonal antibodies were generated in female New Zealand white rabbits, as described previously (Parrow et al, 2009), using 100 mg purified rLimB or rCom1 (Hicks et al, 2010) for both primary and booster injections. Rabbit anti-MBP polyclonal antibodies were purchased (NEB) and used as a negative control for the LimB fusion protein partner.…”
Section: Methodsmentioning
confidence: 99%
“…First, ferredoxin might be involved as an electron transfer agent in biological redox reactions because BCP and Trx activities require NADPH, as discussed previously (Arias et al 2008;Clarke et al 2009;Hicks et al 2010). Second, adenylate kinase is well recognized to play a major role in ATP synthesis, suggesting that the DNA binding by the protein complex and its associated functions require energy (Nitschmann and Peschek 1986).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in this study, the above mentioned protein domains were detected by LC-MS/MS, thus it is possible that Spirulina BCP contains these domains. Furthermore, Hicks et al (2010) reported that BCP is a DNA-binding protein that plays a critical role in detoxifying endogenous hydrogen peroxide byproducts generated from NADPH during the intracellular replication of Coxiella, thus protecting DNA from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have described the expression of a thiol-specific peroxidase (CBU0963) in C. burnetii that belongs to the atypical 2-cysteine subfamily of peroxiredoxins, also designated as bacterioferritin comigratory proteins (BCPs). The implication is that this protein might protect DNA from the Fenton reaction [ 60 ]. Comparison to L. pneumophila , a phylogenetic relative, revealed that C. burnetii rarely encodes any known Fe acquisition or storage proteins, aside from some Fe dependent pathways, as well as the heme biosynthesis pathway and proteins such as SodB.…”
Section: Mechanism Of Intracellular Pathogens For Obtaining Iron Fmentioning
confidence: 99%